Kluyveromyces marxianus from fermented rice and Iranian wine as microbial feed additive for ruminants - Nooraee, Seyed Eeman (2013)
Feeding to manipulate rumen microbial ecosystem and to enhance overall rumen fermentation in order to improve production efficiency of ruminant animals is a main concern for animal nutritionists and rumen microbiologists. Microbial feed additive would be a possible solution. A series of experiments was conducted to isolate and characterize a suitable yeast from traditional fermented rice (Tapai) and home-made wine as a microbial feed additive for ruminants. Yeast isolates were selected based on their tolerance to volatile fatty acids (VFA) mixture of acetic, propionic and butyric acids and to pH and temperature according the rumen condition. The ability to grow and produce ethanol was determined in yeast extract peptone glucose broth supplemented with a VFA mixture. Fifty-five isolates showed optical density, OD660nm, values between 0.35-0.60 and 27 isolates showed ethanol production in the range of 0.17-0.30 (%v/v). All 27 isolates from Tapai and wine were identified as Kluyveromyces marxianus based on biochemical tests or molecular identification using the rDNA nontranscribed spacer 2 region. The best isolate, Kluyveromyces marxianus WJ1, in terms of ethanol production and coutilization of different carbon source with D-xylose was selected for further evaluations. In a 4×4 factorial experiment the effect of alfalfa hay and corn grain ratios (100:0;70:30; 50:50 and 30:70, respectively) and optical density (OD) of Kluyveromyces marxianus WJ1 cell suspension (OD:0.0, OD: 0.1, OD: 0.2 and OD:0.3) as a microbial feed additive on in vitro gas production were examined. Gas production was affected by K. marxianus WJ1 (+11.7%; P<0.01) and substrate significantly (P<0.01). Interaction of K. marxianus WJ1 by substrate was significant (P<0.01). Diphasic model was applied to explain the interaction between K. marxianus WJ1 and substrate. In a completely randomized design, five plant materials, i.e. alfalfa (Medicago sativa), guinea grass (Panicum maximum), bermuda grass (Cynodon dactylon), rice straw (Oryza sativa) and timothy hay (Phleum pretense) were used to evaluate the effect of different K. marxianus WJ1 cells suspensions ( OD: 0.0, OD: 0.1, OD: 0.2 and OD:0.3) on in vitro apparent dry matter digestibility. The in vitro apparent dry matter digestibility of alfalfa (55.0% vs 51.3%), guinea grass (61.0% vs 52.1%) and timothy hay (72.2% vs 62.1%) was improved significantly (P<0.01). The effect of K. marxianus WJ1 on nutrient digestibility, ruminal fermentation and rumen microbial population in goats was evaluated. Treatments were: control (basal diet), basal diet plus 1g freeze dried K. marxianus WJ1 and basal diet plus 5g freeze dried K. marxianus WJ1. Total volatile fatty acid production (92.2 mM vs 82.8 mM; P<0.01) and acetic acid production (66.8% vs 63.8%; P<0.05) were increased when K. marxianus WJ1 (1g) and (5g) was included in basal diet respectively. Ruminal ammonia nitrogen and total protozoa count were reduced significantly (P<0.05) when experimental diet was supplemented by K. marxianus WJ1. A production experiment was conducted to investigate the effect of K. marxianus WJ1 on nutrient digestibility and daily weight gain in goats. Ttreatments were: basal diet (control) and basal diet plus 1g freeze dried K. marxianus WJ1. Organic matter digestibility was increased significantly (P<0.05) compared with control. However, daily weight gain was not significantly affected by treatment. It can be concluded that based on in vitro and in vivo studies, K. marxianus WJ1 could be considered as a potential microbial feed additive for ruminants.